Integrated Area Development as A Sectoral and Regional Development Model (Kuala Tanjung Industrial and Port Area) - Purba, Bintang M; Nuraini, Cut (PT FORMOSA CENDEKIA GLOBAL, 2024)
Integrated area is a multifunctional area concept where each function supports, complements and complements each other, thereby creating optimization of each area function. This research aims to analyze the impact of the Integrated Area (Kuala Tanjung Industrial Area and Port) on development both sectorally and regionally. In this research, the impact of economic development is analyzed through the contribution of the industrial sector to GRDP, GRDP per capita, and the number of workers. The method used is descriptive analysis and Location Quotient (LQ). The research results show that Integrated Areas have a positive impact on economic growth, both sectorally and regionally. The increase in GDP per capita and the consistent role of the Management Industry contributes highly to Batu Bara Regency's GRDP and increases the level of labor absorption. Employment data shows that more than a third (40.97%) of Batu Bara Regency residents work as laborers or employees. The results of the LQ analysis also show that the Industrial Management sector has an average value of 2.48, this shows that the industrial sector has a wider contribution to a region. This shows that the Integrated Area concept is effective in increasing the economic potential of a region and improving community welfare, both at the local and regional levels.